Single-Cell Transcriptomics Identifies Heterogeneity of Mouse Mammary Gland Fibroblasts With Distinct Functions, Estrogen Responses, Differentiation Processes, and Crosstalks With Epithelium - Yoshitake, Ryohei; Chang, Gregory; Saeki, Kohei; Ha, Desiree; Wu, Xiwei; Wang, Jinhui; Chen, Shiuan (Frontiers in Cell and Developmental Biology, 2022)
Fibroblasts have been shown to be one of the essential players for mammary gland organization. Here, we identify two major types of mouse mammary gland fibroblasts through single-cell RNA sequencing analysis: Dpp4+ fibroblasts and Dpp4- fibroblasts. Each population exhibits unique functional characteristics as well as discrete localization in normal mouse mammary glands. Remarkably, estrogen, a crucial mediator of mammary gland organization, alters the gene expression profiles of fibroblasts in a population-specific manner, without distinct activation of estrogen receptor signaling. Further integrative analysis with the inclusion of five other publicly available datasets reveals a directional differentiation among the mammary gland fibroblast populations. Moreover, the combination with the mouse mammary epithelium atlas allows us to infer multiple potential interactions between epithelial cells and fibroblasts in mammary glands. This study provides a comprehensive view of mouse mammary gland fibroblasts at the single-cell level.